2017
DOI: 10.1080/10942912.2016.1238929
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and comparison of key aroma-active compounds of cocoa liquors from five different areas

Abstract: The volatile constituents of cocoa liquor and the differences between cocoa liquors from different origins were studied. Direct solvent extraction-solvent assisted flavor evaporation and gas chromatography-olfactrometry-mass spectrometry in conjunction with aroma extract dilution analysis were used to identify the key flavor compounds in five cocoa liquors. There were significant differences of specific compounds between cocoa liquor from different areas of origins. Then, the purge and trap method was used to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(27 citation statements)
references
References 32 publications
3
23
0
1
Order By: Relevance
“…The most representative compounds of these were acetic acid, tetramethylpyrazine and 2,3-butanediol, similar to those reported in cocoa liquors in different countries (Liu et al, 2017).…”
Section: Volatile Fraction Compoundssupporting
confidence: 59%
See 1 more Smart Citation
“…The most representative compounds of these were acetic acid, tetramethylpyrazine and 2,3-butanediol, similar to those reported in cocoa liquors in different countries (Liu et al, 2017).…”
Section: Volatile Fraction Compoundssupporting
confidence: 59%
“…Nonetheless, the quality of the product depends on the chemical reactions that occur, and are characterized by organoleptic qualities described by basic, specific and acquired tastes; furthermore, aromas found in volatile components of cocoa liquor are also present (Liu, Liu, He, Song, Liu, Zhang & Su, 2017;Rivera, Mecias, Guzmán, Peña, Medina, Casanova,… Nivela, 2012). Owing to its high organoleptic qualities, which are obtained through sensory tasting panels.…”
Section: Introductionmentioning
confidence: 99%
“…Quadrupole time‐of‐flight mass spectrometry (Q‐TOF‐MS) is able to combine high sensitivity and mass accuracy for both precursor and product ions and, therefore, allows the elemental composition for both parent and fragment ions to be confirmed both quickly and efficiently. UHPLC can provide high resolutions for the separation of complicated natural products and improves the sensitivity of Q‐TOF‐MS detectors (Li et al., ). In this study, the authors observed how protein quantities, and their profiles derived from two‐dimensional gel electrophoresis, showed striking differences for nonfermented beans depending on their geographical origin.…”
Section: Determination Of Cocoa Componentsmentioning
confidence: 99%
“…Many studies about the determination and/or changes produced in the flavor, aroma, and taste during cocoa fermentation (Crafack et al., ), roasting (Torres‐Moreno et al., ), among different cocoa clones or varieties (Liu et al., ), and among different cocoa products (Chetschik et al., ) have been recently published. Torres‐Moreno et al.…”
Section: Determination Of Cocoa Componentsmentioning
confidence: 99%
See 1 more Smart Citation